Study on Instant Delivery Service Riders' Safety and Health by the Effects of Labour Intensity in China: A Mediation Analysis - Chen, Tianxue; Tian, Dazhou; Deng, Peihua; Zhou, E.; Huang, Jinjin (Frontiers in Public Health, 2022)
Instant Delivery Service (IDS) riders' overwork by “self-pressurization” will not only reduce the level of their physical and mental health, but also lose their lives in safety accidents caused by their fatigue riding.Based on Cobb-Douglas production function in the input-output theory,this study characterized the factors on IDS riders' safety and health associated with labor intensity.A mediating model with moderating effect was adopted to describe the mediation path for the 2741 IDS riders who were surveyed.The results of moderating regression demonstrated that (1)0.4655 is the total effect of labor intensity on the safety and health of IDS riders. (2) 0.3124 is the moderating effect that working hours make a greater impact on labor intensity.(3)the mediating effect of job pressure is the leading mediation path at both the front-end and the back-end.